The Grid and the Cloud How to Connect : HISK Laureates 2017 : Curator: Elena Sorokina. - Lovink, Geert; Sorokina, Elena (Gent : HISK/Hoger Instituut voor Schone Kunsten, 2017)
buren ; de Burca, Ella ; De Vos, Kasper ; Faassen, Vesna & Verdijk, Lukas ; Gaisumov, Aslan ; Ghekiere, Elias ; Ivanova, Pepa ; Lanko, Ola ; Löffler, Rebekka ; Loze, Ariane ; Lutgens, William Ludwig ; Navarro, Cadine ; Paepens, Jonathan
The Grid and the Cloud: How to Connect, Vanderborgt Building, Brussels, 24 November till 17 December 2017
boek